2009
DOI: 10.1021/es9003735
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Contaminated Soil and Airborne Particulates to Indoor Dust

Abstract: We have developed a modeling and measurement framework for assessing transport of contaminated soils and airborne particulates into a residence, their subsequent distribution indoors via resuspension and deposition processes, and removal by cleaning and building exhalation of suspended particles. The model explicitly accounts for the formation of house dust as a mixture of organic matter (OM) such as shed skin cells and organic fibers, soil tracked-in on footwear, and particulate matter (PM) derived from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 54 publications
2
65
0
Order By: Relevance
“…Recalling the fact that most coarse particles are actually dust particles, the indoor air of carpeted Offices A1 and A2 contained more dust particles than the uncarpeted Offices B1 and B2. Therefore, we assume that carpets accommodate dust deposits more efficiently than bare floors (Layton and Beamer, 2009). Furthermore, occupancy and moving around inside an office increases the mechanical re-suspension of dust particles; and thus, increases the concentration of coarse particles indoors (Meyer et al, 1999).…”
Section: Average Concentrations: Occupancy Versus Vacancymentioning
confidence: 99%
“…Recalling the fact that most coarse particles are actually dust particles, the indoor air of carpeted Offices A1 and A2 contained more dust particles than the uncarpeted Offices B1 and B2. Therefore, we assume that carpets accommodate dust deposits more efficiently than bare floors (Layton and Beamer, 2009). Furthermore, occupancy and moving around inside an office increases the mechanical re-suspension of dust particles; and thus, increases the concentration of coarse particles indoors (Meyer et al, 1999).…”
Section: Average Concentrations: Occupancy Versus Vacancymentioning
confidence: 99%
“…The contribution of lead emissions in the air to the contamination of interior floor dust was estimated as very low (only a few percent), even for the highest observed values; moreover, there was no evidence of its effect. Layton and Beamer (2009) demonstrated that airborne lead was the main source of lead in interior floor dust by analyzing data on lead contamination in Sacramento, CA, United States, in the early 1980s and assumed that after the phase-out of leaded gasoline, soil track-in was the major source of lead contamination of interior floor dust. Our results are quite consistent with this assumption.…”
Section: Sources Related To the Outdoor Environmentmentioning
confidence: 99%
“…Polluting sites (Davies et al, 1985), (Cook et al, 1993), Contaminated sites (Davies et al, 1987), (Lanphear and Roghmann, 1997), , (Clark et al, 2004), (Hunt et al, 2006) Lead emissions in air (Layton and Beamer, 2009) Smoking inside (Gaitens et al, 2009) XRF sum-deteriorated (Sturges and Harrison, 1985), (U.S. HUD, 1995), (Lanphear and Roghmann, 1997), (Farley, 1998), (Succop et al, 1998), (CDC, 2007), (Beauchemin et al, 2011), (Dixon et al, 2012) XRF sum-usual condition…”
Section: Covariate Label Studiesmentioning
confidence: 99%
“…However, it is possible that pesticides are primarily entering the home via air infiltration of agricultural spray drift and resuspended soil. In another study it was determined that approximately 60% soil contaminants present in house dust are from air infiltration of resuspended soil rather than soil track-in on shoes (Layton and Beamer 2009). In addition to presence of farmworkers in the home, household proximity to fields where pesticides have been applied is also associated with pesticide levels in house dust , McCauley et al 2001.…”
Section: Future Directionsmentioning
confidence: 99%